An unusual case of invasive papillary carcinoma of the breast - Aysen Terzi; Aysegul Hasegeli Uner (Wolters Kluwer Medknow Publications, 2012)
Invasive papillary carcinoma is a rare variant of breast cancer. We report an unusual case of invasive papillary carcinoma of the breast with high nuclear grade, brisk mitosis, necrosis, extensive apocrine differentiation, and intense lymphoplasmacytic infiltrate; additionally triple-negativity for estrogen and progesterone receptors and Her2 neu. The patient underwent modified radical mastectomy and adjuvant chemotherapy. But, it was a node negative breast carcinoma. Increasing the awareness of this clinicopathologic entity would be helpful in avoiding overtreatment of patients with this cancer even if the tumor has negative morphological and immunohistochemical prognosticators.